Management of Physiotherapy In Brachial Plexus Injury Post Neurotization SAN To SSN : Case Report - La Ode Abdul Haris Hijriansyah (Jurnal Kesehatan LLDikti Wilayah 1 (JUKES), 2021)
Brachial plexus injury (BPI) is an injury to the brachial plexus that can cause muscle paralysis in the upper extremities. Based on the data, the proportion of brachial plexus injuries with total lesions (C5–T1) was 54%, partial lesions (C5-6) 24%, (C5-C7) 19%, and (C8-Th1) 3%. This case report aims to present the physiotherapy management of brachial plexus injury. A 23-year-old man with a medical diagnosis of brachial plexus injury. Previously the patient fell from the bathroom and suffered a blow to the shoulder and fractures in the proximal 1/3 of the ulna & radial. The patient received the first medical treatment for fracture with ORIF (plate and screw), while the shoulder injury received medical treatment after 6 months. The medical procedure is SAN to SSN neurotization surgery. The physiotherapy program provided include ROM exercise, strengthening, stretching, and release. The results of the evaluation for 3 times of therapy showed that there was a change in passive ROM, pain, edema and spasm in the shoulder region. there has been no change in muscle strength and sensory function. In addition, in the wrist and elbow region there is an increase in muscle strength. The process of nerve recovery takes a long time, so there have not been many changes that have occurred in the patient. The process of nerve growth only occurs at 1 mm / day. Physiotherapy program given for 3 days postoperative conditions only aim to reduce problems such as muscle spasm, edema, postoperative pain, muscle tightness, and prevent potential problems that will occur. The physiotherapy program given can reduce secondary problems that occur in the condition 3 days after brachial plexus injury.